Updating Practice Recommendations: Taking Stock of 12 Years of Adolescent Literacy Research. Issue 1 (14th June 2021) - Reynolds, Dan
Abstract: The demand for evidence to support instructional practices in education is surging. Consequently, many adolescent literacy researchers and educators take guidance from the Institute of Education Sciences (IES) Practice Guide for Adolescent Literacy (Kamil et al., 2008). The document, however, is now 12 years old, and adolescent literacy research and practice has shifted substantially. First, I document the limitations of the IES Guide's pre‐2008 research base and of the students sampled in its underlying studies. Then, I survey research from 2008–2020 that expands on the Guide's five recommendations, and name areas of research undeveloped in 2008 but vibrant in 2020. To illustrate the instructional implications of these changes, I present an example unit incorporating changes suggested by research since 2008. Finally, I call on adolescent literacy organizations to maintain, revise, and publish practice guidelines to ensure all our adolescents get the daily literacy instruction they deserve.